ANALISIS FAKTOR YANG MEMPENGARUHI PRODUKSI, BIAYA DAN PENDAPATAN PENGUSAHA INDUSTRI SKALA KECIL KAYU OLAHAN DI KABUPATEN SIJUNJUNG - Febria Rahim (LPPM - STIE SAKTI ALAM KERINCI, 2019)
The development of small-scale industrial processed wood in Sijunjung district is one of the industries that needs to be developed, this is because Sijunjung has extensive production forests as a source of wood raw material. Many factors influence the development of this wood processing industry, including production costs and income the progress of an industry. This study aims to analyze and determine the factors that influence the production of costs and revenues in small-scale industrial processed wood in Sijunjung District. The method used in this study is descriptive and associative, and uses simultaneous equation modeling tools with the indirect Least square (ILS) method. The study population was 60 small-scale industrial producers of wood defeats in Sijunjung district and 52 samples were used in the processed wood industry. The results showed that (1) the amount of logs and the amount of fuel partially had a significant effect on processed wood production, an increase in the number of logs and the amount of fuel would encourage an increase in processed wood production. Meanwhile the number of workers does not have a significant effect on processed wood production, the increase in the number of workers does not encourage an increase in processed wood production in Sijunjung Regency. (2) The amount of production, the labor wage price of fuel and the price of roundwood partially have a significant effect on processed wood production. (3) The amount of production, selling price and level of education and work experience of producers have a significant effect on the income of processed wood producers in small-scale industrial processed wood in Sijunjung Regency.